2014
DOI: 10.1123/jtpe.2013-0107
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Interest and Performances in Aerobic Fitness Testing

Abstract: This study examined adolescents' interest in aerobic fitness testing and its relation to the test performances. Adolescents (N = 356) from three middle schools participated in the study. The participants took two aerobic fitness tests: the Progressive Aerobic Cardiovascular Endurance Run (PACER) and One-Mile Run (1MR) with a two-day interval, and completed two interest scales immediately after each test. Test performances, interest, and body mass index data were collected. Data were analyzed using descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…An exploratory study that investigated the factors that influence high school girls’ enrolment in elective physical education (Davis et al, 2018) indicated that students ( n = 17) acknowledged the importance of HRPF, but desired less of a focus on fitness testing. Similarly, Zhu et al (2014) found that boys reported significantly higher situational interest in the PACER (progressive aerobic cardiovascular endurance run) test in comparison to girls. Engaging girls in physical education has been reported as a challenge for teachers across most aspects of the curriculum (Enright and O’Sullivan, 2010), but particularly so when it comes to fitness testing (Davis et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…An exploratory study that investigated the factors that influence high school girls’ enrolment in elective physical education (Davis et al, 2018) indicated that students ( n = 17) acknowledged the importance of HRPF, but desired less of a focus on fitness testing. Similarly, Zhu et al (2014) found that boys reported significantly higher situational interest in the PACER (progressive aerobic cardiovascular endurance run) test in comparison to girls. Engaging girls in physical education has been reported as a challenge for teachers across most aspects of the curriculum (Enright and O’Sullivan, 2010), but particularly so when it comes to fitness testing (Davis et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…However, the growth rate was unequal between girls and boys, which may have contributed to the performance gap at the 11th grade. Research showed that boys outperform girls in physical fitness tests (Zhu et al, 2014). While the physical fitness test difference can be attributed to different developmental trajectories between boys and girls, a better understanding of the growth rate differences in health-related fitness knowledge is needed.…”
Section: Discussionmentioning
confidence: 99%
“…For one, students may have been more motivated initially to ride the bike than they were the second time. Research has shown that situational interest, the engaging effect of an activity on individuals (Schiefele, 2009), has the ability to elicit these results (Sun, 2012;Zhu, Chen, & Parrott, 2014). Situational interest is perceived as a two-state framework (Schiefele, 2009).…”
Section: Discussionmentioning
confidence: 99%